Lexical Change: Naming of the Months of the Year in Ekegusii - Maroko, Geoffrey M.; Morara, Jacqueline N. (Journal of Applied Linguistics and Language Research, 2016)
This paper documents the native terms used to name the months of the year in EkeGusii. EkeGusii is a language spoken by a Bantu speaking community (AbaGusii) in the South Western part of Kenya. It is a language with a rich cultural heritage manifested in elaborate cultural values, beliefs, traditions. The Kenyan society is multilingual with over sixty-seven languages. In order to transact Government business and ensure inter-ethnic communication, the Kenya Constitution (2010) identifies English and Kiswahili as co-official languages with Kiswahili doubling up as the national language. The two languages of wider communication have relegated the use of ethnic languages mostly to intra-ethnic interactions particularly among the aging populace. Consequently, ethnic languages such as EkeGusii are potentially endangered. Evidence for such endangerment is a shift from the use of native terms used to refer to the months of the year in EkeGusii to new names borrowed from English and Kiswahili. Further, there is no apparent intervention aimed at revitalizing the rich cultural side to the language of the AbaGusii people. Yet the Kenya Constitution (2010) calls for the protection and preservation of Kenyan languages which are threatened with extinction. To plug this research gap, this paper establishes the native names of the months of the year and their meanings and juxtaposes them to the new loan words from English and Kiswahili. The paper recommends consciousness-raising strategies such as introduction of EkeGusii programmes in local radio stations to popularize fading names with rich cultural meaning.
Keywords: Lexical change; Revitalization; Native names